Suitability of bamboo brick as a lightweight construction material / Noor Zuraida Jusoh - Jusoh, Noor Zuraida (Institute of Graduate Studies, 2017)
The increasing issues of pollution create awareness that leads to the close down of some mining sand quarries. The usage of river sand as an alternative resources also contributed to pollution. Consumption of sand must be reduced in order to stop its negative impact on environment. Bamboo is the alternative raw material in construction that is used for bricks and concrete. Bamboo is one of the fastest growing plants, abundant and low cost material. Many studies were done on bamboo especially on mechanical and physical properties of Semantan bamboo (Gigantochloa scortechinii). However, there is no study on the properties of Akar bamboo (Dendrocalamus pendulus). Therefore, one of the objectives of this thesis was to evaluate the properties of Akar bamboo and as well as Semantan bamboo as a lightweight construction materials. The basic properties of bamboo evaluated were compressive strength, specific gravity, water absorption and dimensional stability. Bamboo skin can significantly increase compressive strength and significantly reduce water absorption and dimensional stability of bamboo. The presence of nodes in bamboo significantly reduce the compressive strength. In this study, waterproof coating was used in bamboo brick samples. The usage of waterproof coating has significantly reduced water absorption and dimensional changes of bamboo. The waterproofing agent like Axel Deram however not only act as water barrier but can provide good bonding strength when bamboo was embedded into cement mortar..